LAG-3–associated CD8+ T-cell dysfunction in the cervical cancer tumor microenvironment - Zhang, Guang; Wang, Lei; Chen, Jianhuan; Wang, Jing; Ainiwaer, Abidan; Ma, Cailing (Frontiers in Immunology, 2026)
IntroductionCytotoxic T lymphocytes (CTLs, mainly CD8+ T cells) are the primary killer cells in the tumor microenvironment (TME). This study investigates the expression of LAG-3 in the TME of cervical cancer and its regulatory role in CD8+ T cell function.MethodsCervical tissue pathological sections and fresh cervical tissues were collected from patients with cervical cancer, patients with high-grade squamous intraepithelial lesion (HSIL), and patients who underwent hysterectomy for non-cervical diseases (without a history of other tumors). Immunohistochemistry, Western blotting, quantitative real-time PCR, and fluorescence imaging techniques were used to analyze the expression of LAG-3 in the cervical cancer TME and its correlation with clinical tumor stage, differentiation grade, lymph node metastasis status, and lymphovascular space invasion. A cell co-culture system and a cervical cancer mouse model were established to evaluate the effects of lag-3 on tumor growth and changes in CD8+ T cell function.ResultsLAG-3 is highly expressed in the tumor microenvironment (TME) of cervical cancer, with its expression level increasing as the tumor stage progresses: the lower the degree of differentiation, the higher the LAG-3 expression; LAG-3 expression is also elevated in cases with lymph node metastasis and lymphovascular space invasion. In vivo mouse models confirmed that lag-3 inhibits CD8+ T cells from expressing Ki67, T-bet, TNF-α, IFN-γ, and IL-2. Furthermore, we found that lag-3 not only suppresses the differentiation of naive CD8+ T cells into central memory T cells (TCM) but also inhibits the differentiation of TCM into effector memory T cells (TEM), a subset with stronger anti-tumor effector functions. A similar phenomenon was observed in cell co-culture experiments.DiscussionWe confirmed that LAG-3 is highly expressed in cervical cancer tissues and is closely correlated with clinical stage, differentiation grade, lymph node metastasis, and lymphovascular space invasion. LAG-3 may inhibit the function of CD8+ T cells in the cervical cancer TME, thereby promoting the progression of cervical cancer.